ANALISIS METODE PENYUSUTAN AKTIVA TETAP (PAJAK) PERUSAHAAN MENGGUNAKAN MS. EXCEL - Suhartono, Suhartono (www.bsi.ac.id, 2010)
One each company must have tangible fixed asset and also one abstracts since asset constitute medium for corporate deep going operational activity, as building or building as office, machine and equipment to get production, vehicle as tool for transportation, etc. as it who can back up all corporate activity. Fixed asset usually have using up term that so long, so is expected gets to give benefit for corporate for many years. But such, benefit that given by fixed asset by and large getting long time gets menurun its using up continually, and causes depreciation happening. Depreciation is process allocation a portion asset derived price become cost (cost allocation) . Depreciation will ascendant to outgrow its unrealized little that acquired of arithmetic fiscal (taxes). Noted depreciation and is reported by use of depreciation methods for example taxation terminological methods